Evaluación de conocimientos en la atención clínica odontológica a pacientes diagnosticados con trastornos de la hemostasia (2021)
The latest study conducted in Colombia by the Ministry of Health and Social Protection, determined that there are 4,606 people diagnosed with some coagulopathy, in addition it is established that these disorders present a great professional challenge in dental care, which requires skill and clarity in pharmacological knowledge, hemostasy maneuvers and antifibrinolytic agents.